Audit Implications of Non‐GAAP Reporting - HALLMAN, NICHOLAS J.; SCHMIDT, JAIME J.; THOMPSON, ANNE M. (Journal of Accounting Research, 2022)
ABSTRACT We investigate whether non‐GAAP reporting affects the audit process and thereby the quality of the related financial statements. First, we provide evidence that auditors in numerous countries, including the United States and the United Kingdom, rely to varying degrees on non‐GAAP profit before tax as a benchmark for determining quantitative materiality. Then, using Premium Listed companies on the London Stock Exchange, we document that U.K. auditor reliance on non‐GAAP materiality benchmarks often results in a higher quantitative materiality amount and can lower audit quality. Although U.K. auditors appear skeptical of managers’ more aggressive non‐GAAP adjustments, auditors adopt more of management's low‐quality adjustments when auditor independence is weaker. In sum, our results suggest that non‐GAAP reporting can indirectly affect investors by reducing the rigor of the financial statement audit.